Including access and benefit sharing in the Post-2020 Global Biodiversity Framework: a submission from the Alliance of Bioversity International and the International Center for Tropical Agriculture - Alliance of Bioversity International and CIAT (2019)
The Alliance of Bioversity International (Bioversity) and the International Center for Tropical Agriculture (CIAT) is making this submission to the 23rd meeting of the Convention on Biological Diversity’s Subsidiary Body on Scientific, Technical and Technological Advice (SBSTTA 23) as a contribution to the development of the Post-2020 Global Biodiversity Framework (Post-2020 Framework). This submission focuses on how access and benefit-sharing rules and practices could be included in the post-2020 framework. In summary, we propose that consideration of access and benefit-sharing issues in the Post-2020 Framework should expand beyond Aichi Target 16’s exclusive focus on the Nagoya Protocol, and promote the broader, mutually supportive implementation of the Nagoya Protocol and the International Treaty on Plant Genetic Resources for Food and Agriculture.